Analysis of GLUT-1, GLUT-3, and angiogenic index in syndromic and non-syndromic keratocystic odontogenic tumors - Rafaella Bastos LEITE; Roberta Barroso CAVALCANTE; Renato Luiz Maia NOGUEIRA; Lélia Batista de SOUZA; Leão PEREIRA PINTO; Cassiano Francisco Weege NONAKA (Sociedade Brasileira de Pesquisa Odontológica, 2017)
Abstract The aim of this study was to evaluate the immunoexpression of glucose transporters 1 (GLUT-1) and 3 (GLUT-3) in keratocystic odontogenic tumors associated with Gorlin syndrome (SKOTs) and non-syndromic keratocystic odontogenic tumors (NSKOTs), and to establish correlations with the angiogenic index. Seventeen primary NSKOTs, seven recurrent NSKOTs, and 17 SKOTs were selected for the study. The percentage of immunopositive cells for GLUT-1 and GLUT-3 in the epithelial component of the tumors was assessed. The angiogenic index was determined by microvessel count. The results were analyzed statistically using the nonparametric Kruskal-Wallis test and Spearman's correlation test. High epithelial immunoexpression of GLUT-1 was observed in most tumors (p = 0.360). There was a higher frequency of negative cases for GLUT-3 in all groups. The few GLUT-3-positive tumors exhibited low expression of this protein in epithelial cells. No significant difference in the angiogenic index was observed between groups (p = 0.778). GLUT-1 expression did not correlate significantly with the angiogenic index (p > 0.05). The results suggest that the more aggressive biological behavior of SKOTs when compared to NSKOTs may not be related to GLUT-1 or GLUT-3 expression. GLUT-1 may play an important role in glucose uptake by epithelial cells of KOTs and this process is unlikely related to the angiogenic index. GLUT-1 could be a potential target for future development of therapeutic strategies for KOTs.